Construction management - Halpin, Daniel W. (John Wiley and Sons, 1998)
This book introduces to the basic topics which structure the complex business of developing and constructing a major facility or structure. The analogy of construction management being like the multifaceted challenges confronted by the decathalon athlete still holds up...